Electrophysiological Mechanism and Identification of Effective Compounds of Ginger (Zingiber officinale Roscoe) Shoot Volatiles Against Aphis gossypii Glover (Hemiptera: Aphididae) - Jiawei Ma; Ye Tian; Xuli Liu; Shengyou Fang; Chong Sun; Junliang Yin; Yongxing Zhu; Yiqing Liu (Horticulturae)
Aphis gossypii Glover (Homoptera: Aphidinae), a major pest of Chinese pepper (Zanthoxylum bungeanum Maxim), causes significant agricultural damage. Ginger (Zingiber officinale Roscoe) has shown potential as a source for developing botanical pesticides due to its strong bacteriostatic and insecticidal properties; however, the underlying mechanisms remain poorly understood. This study evaluated the repellent activity of ginger shoot extract (GSE) across four solvent phases—petroleum ether, trichloromethane, ethyl acetate, and methanol—against A. gossypii. The results demonstrated that GSE exhibited significant repellent effects, with the methanol phase showing the most pronounced activity. Twelve fractions were chromatographically separated from the methanol phase, and electroantennography (EAG) analysis revealed that fraction 4 induced strong EAG responses in both winged and wingless aphids. Further identification of active compounds in fraction 4 by gas chromatography–mass spectrometry (GC–MS) indicated the presence of terpenes, aromatics, alkanes, esters, and phenols as major constituents. Subsequent EAG analysis identified several key compounds—octahydro-pentalene (C1), (Z)-cyclooctene (C2), dimethylstyrene (C3), tetramethyl-heptadecane (C5), tetrahydro-naphthalene (C6), and heptacosane (C9)—as responsible for eliciting EAG responses in both aphid forms. Additionally, results from Y-tube olfactometer assays showed that (Z)-cyclooctene and heptacosane were significantly attractive, while octahydro-pentalene acted as a strong repellent to both winged and wingless aphids. These findings offer valuable insights for the development of synthetic attractants and repellents for A. gossypii and provide a theoretical foundation for utilizing ginger in the creation of botanical pesticides targeting this pest.